2022
DOI: 10.1038/s42003-022-03107-3
|View full text |Cite
|
Sign up to set email alerts
|

Climate-change-driven growth decline of European beech forests

Abstract: The growth of past, present, and future forests was, is and will be affected by climate variability. This multifaceted relationship has been assessed in several regional studies, but spatially resolved, large-scale analyses are largely missing so far. Here we estimate recent changes in growth of 5800 beech trees (Fagus sylvatica L.) from 324 sites, representing the full geographic and climatic range of species. Future growth trends were predicted considering state-of-the-art climate scenarios. The validated mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
95
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(107 citation statements)
references
References 65 publications
8
95
2
2
Order By: Relevance
“…Currently, F. sylvatica suffers extensive growth reductions in large parts of Europe [93], with climate-related forest declines in the southern parts of its expansion also documented [94]. Empirical models based on dendroecological data project severe growth declines during the 21st century [95]. Our projections predict a strong decrease in beech habitat suitability under both climate scenarios, accompanied by a strong elevation shift, in agreement with other models that suggest that the species might expand its northern edge and lose habitat at the southern edge of its distribution under a warmer and drier climate [96].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, F. sylvatica suffers extensive growth reductions in large parts of Europe [93], with climate-related forest declines in the southern parts of its expansion also documented [94]. Empirical models based on dendroecological data project severe growth declines during the 21st century [95]. Our projections predict a strong decrease in beech habitat suitability under both climate scenarios, accompanied by a strong elevation shift, in agreement with other models that suggest that the species might expand its northern edge and lose habitat at the southern edge of its distribution under a warmer and drier climate [96].…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the recent and relatively swift change in disturbance regimes and weather patterns, which are significantly altering the ecological niches of tree species on a temporal scale of less than a few decades instead of centuries. The impact of these changes on tree species has become more noticeable from year to year, with growth decline ( Martinez del Castillo et al, 2022 ) and increased mortality rates ( Senf, Sebald & Seidl, 2021 ; Senf et al, 2018 ) demonstrated in literature as already occurring across large forested areas. Including the temporal domain in tree species distribution studies is therefore fundamental to capture the temporal evolution of these change processes.…”
Section: Introductionmentioning
confidence: 99%
“…Questa trasformazione ha in parte compromesso resistenza e resilienza delle foreste che sono poi state ulteriormente indebolite dagli stress climatici provocati dai cambiamenti globali. Le conseguenze di questi processi sono il manifestarsi di fenomeni di deperimento (Vacchiano et al 2012, Haavik et al 2015, Camarero et al 2017, un aumento della mortalità conseguente a disturbi naturali o ad interazione tra disturbi naturali (Schelhaas et al 2003, Seidl et al 2011, un aumento della mortalità conseguente ad estremi climatici (Allen et al 2010, Senf et al 2020) ed una diminuzione dell'accrescimento di diverse specie (Bosela et al 2021, Martinez Del Castillo et al 2022. Le foreste europee, anche se complessivamente sono in fase di espansione ed aumento della biomassa legnosa per unità di superficie (Forest Europe 2020), sono quindi in sofferenza e vedono già oggi, ma ancora di più in prospettiva, diminuita o compromessa la loro capacità di erogare alcuni servizi ecosistemici (Mina et al 2017, Seidl et al 2019.…”
Section: Selvicoltura Più Vicina Alla Naturaunclassified